Pengaruh Produk Domestik Bruto, Cadangan Devisa Dan Kurs Dollar Amerika Serikat Terhadap Impor Produk Elektonik Di Indonesia Tahun 1993 – 2013 - Kencana Dewi, Putu Tjintia; Sudiana, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
The purpose of this study to determine the effect of gross domestic product, foreign exchange reserves and the exchange rate against the US dollar imports of electronic products in Indonesia in 1993-2013. Analysis of the data used is multiple linear regression analysis with the help of SPSS software. The data used in this analysis is the secondary data. The analysis showed gross domestic product (GDP), foreign exchange reserves and the US dollar exchange rate simultaneously significant effect on imports of electronic products in Indonesia in 1993-2013. Gross domestic product and foreign exchange reserves partially positive and significant impact on the import of electronic products in Indonesia in 1993-2013. US dollar exchange rate partially negative and significant effect on imports of electronic products in Indonesia in 1993-2013.
Keywords: Produk Domestik Bruto; Cadangan Devisa; Kurs Dollar Amerika; Impor Produk Elektronik